“A Bridge Between Imagination and Reality Must Be Built”: Film and Spatial Critique in the Work of Patrick Keiller - Kinik, Anthony (Intermédialités / Intermediality)

(untitled) (Revue Intermédialités (Presses de l’Université de Montréal), 2009)
This essay expands upon the existing scholarship on Patrick Keiller by taking into consideration his extra-filmic career as a writer and scholar and especially his writings on film, art history, and geography. This perspective underlines Keiller’s participation in a tradition of aesthetic and critical engagements with the built environment that dates back to the late-19th and early-20th centuries, one with important implications for cinema. The essay concludes with a close reading of Robinson in Space (1997) that highlights Keiller’s approach to using film as a medium of spatial critique.